Influence of bacteriobilia on postoperative complications in patients with periampullary tumors - Svatoň, Roman; Procházka, Vladimír; Hanslianová, Markéta; Kala, Zdeněk (Asian journal of surgery, 2023)
BACKGROUND: Periampullary tumours (PAT) may cause obstruction of distal choledochus. The bile stasis is a risk factor for microbial colonisation of bile (bacteriobilia), cholangitis, hepatic insufficiency and coagulopathy. PAT obstruction can be managed surgically or non-operatively - by inserting a biliary drain or stent (BDS). Although BDS allows for adequate bile drainage, liver function restitution and coagulopathy, increased bacteriobilia has been reported and this is associated with an increased incidence of postoperative complications. METHODS: A monocentric, prospective, comparative study including 100 patients operated with PAT. The effects of bacteriobilia and the presence of a drain in the biliary tract on the development of postoperative complications were evaluated. RESULTS: Positive microbial findings in bile were found in 67% of patients. It was 98% in the biliary drain group vs. 36% in non-drained patients (p = 0.0001). In 68% 2 or more different bacterial strains were simultaneously present (p = 0.0001). Patients with a positive microbial finding in bile had more frequent incidence of infectious complications 40.2% (27) vs. 9.1% (3); p = 0.0011. The most frequent infectious complication was wound infection 29.8% (20) vs. 3.03% (1); p = 0.0014. Similarly, a higher incidence of postoperative infectious complications occurred in patients with BDS - 36% (18) vs. 24% (12); p = 0.2752. CONCLUSION: The presence of a drain or stent in the biliary tract significantly increases the microbial colonisation of bile. It is associated with a significant increase in infectious complications, especially infections in the wound.
Keywords: Cholestasis; nádory; Postoperative Complications; pooperační komplikace; Humans; Cholangitis; cholangitida; prospektivní studie; lidé; cholestáza; Neoplasms; Prospective Studies